Quality of life on hemodialysis and inflammation: a descriptive analysis - M.R. Bacci; F. Adami; F.W.S. Figueiredo; B.C.A. Alves; G.L. da Veiga; F.L.A. Fonseca (Brazilian Journal of Medical and Biological Research, 2018)
Chronic kidney disease (CKD) is highly prevalent worldwide. Patients with CKD on hemodialysis are more likely to present behavioral changes and worse quality of life as a result of their routine and complications. They also have higher levels of cytokines. The aim of this study is to assess the relationship between the inflammatory profile and quality of life measured by KDOQL-SF36 in hemodialysis outpatients. Patients older than 21 years of age and on routine hemodialysis for at least 6 months with treatment on a regular weekly basis were included and their anthropometric parameters and serum inflammatory markers were evaluated. Thirty patients consented to participate. Homocysteine (Hcy) levels were correlated with worse glomerular filtration rate (GFR; P=0.003) and creatinine (P=0.002). IL-6 was not correlated with worse nutritional status taking into account body mass index (BMI; kg/m2; P=0.83). On the other hand, TNF-alpha was positively correlated with albumin (P=0.008), nutritional status by BMI (P=0.04), and nutritional status by arm circumference area (P=0.04). IL-6 was correlated with activity limitation (P=0.02) and Hcy with work status (P=0.04). Hcy was correlated with nutritional status and inflammatory markers. In this population, the majority of the sections in KDOQL-SF36 were not correlated with cytokines levels.